2014
DOI: 10.1007/s10551-014-2467-2
|View full text |Cite
|
Sign up to set email alerts
|

CEO Accountability for Corporate Fraud: Evidence from the Split Share Structure Reform in China

Abstract: We use institutional-related theories and a unique natural experiment that enables an exogenous test of the influence of controlling shareholders on managerial accountability to corporate fraud. In China, prior to the Split Share Structure Reform (SSSR), state shareholders held restricted shares that could not be traded. This restriction mitigated state-owned enterprise controlling shareholders' incentives to monitor managers. The data examined show the SSSR strengthens incentives of stateowned enterprise cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 150 publications
3
29
0
Order By: Relevance
“…Corporate governance variables play important roles in predicting CEO dismissal (Chen, Cumming, Hou, & Lee, ). Research has shown analyst coverage (Wiersema & Zhang, ) and institutional ownership (Parrino, Sias, & Starks, ) can predict CEO dismissal; therefore, we control for analyst coverage and institutional ownership.…”
Section: Methodsmentioning
confidence: 99%
“…Corporate governance variables play important roles in predicting CEO dismissal (Chen, Cumming, Hou, & Lee, ). Research has shown analyst coverage (Wiersema & Zhang, ) and institutional ownership (Parrino, Sias, & Starks, ) can predict CEO dismissal; therefore, we control for analyst coverage and institutional ownership.…”
Section: Methodsmentioning
confidence: 99%
“…However, some studies report that investors and customers favour companies with state ownership, because state ownership is considered as an indicator that these companies have access to resources controlled by the state and may receive some support from the state when facing difficult situations (Ramírez and Tan, 2004;Spicer and Okhmatovskiy, 2015). This argument is supported by studies of CEO turnover in China, demonstrating that state-owned companies are reluctant to replace CEOs when corporate fraud is discovered (Chen et al, 2016;Cumming, Hou and Lee, 2011). The state often holds shares of companies to pursue goals of long-term economic development, and thus state investments represent a source of patient capital, especially in emerging economies (Musacchio and Lazzarini, 2014).…”
Section: Moderating Role Of Ownershipmentioning
confidence: 99%
“…The papers in this special issue offer further evidence on related topics of the effect of fraud in China. Chen et al (2016b) audit firm in China due to a major audit failure. They find that the market shares and audit fees of these partners fell, and that these partners are less likely to be employed by other reputable audit firms.…”
Section: Corporate Fraudmentioning
confidence: 99%